Cultivating Congregational Music Talents: Band Training Strategy in GKJ Sampangan Kradenan - Ramaputra, Nathaniel Dhiar; Susetyo, Bagus (Jurnal Seni Musik, 2025)
This research examines the band music training strategy at GKJ Sampangan Kradenan, Semarang, as a community learning phenomenon without a permanent trainer and formal curriculum. The phenomenon shows how the church community can nurture the musical talents of the congregation through a flexible, collaborative, and participatory approach. The research used a descriptive qualitative method through a case study, using participatory observation, interviews, and documentation techniques. The results show that the band music training in this church relies on the spirit of cooperation, collective responsibility, and shared learning practices that demonstrate the principles of Community of Practice (Wenger, 1998). Although informal, this strategy proved effective in building team cohesiveness, improving musical quality, and fostering active participation from various layers of the congregation in church music ministry.